2012
DOI: 10.1111/j.1751-1097.2012.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

UVB Radiation Affects Growth, Reproduction and Tissue Structure of Daphnia magna Across Several Temperatures

Abstract: We examined the effects of daily exposure to UVB on growth, reproduction and histological characteristics of Daphnia magna over two generations at 20, 22, 25 and 30°C. Animals were exposed to 16 h of UVA and photosynthetically active radiation daily. Treated animals received 6 h of UVB during the light phase. Parental (P) generation growth and reproduction was impaired by exposure to UVB at all temperatures, with the poorest production at 30°C. First brood size decreased with UVB exposure; it was lowest at 30°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Similar life-history effects of UV exposure have been reported for other aquatic taxa, including amphibians (e.g. Pahkala, Laurila & Meril€ a 2001;Pahkala et al 2003) and cladocerans (Huebner et al 2013). The delayed metamorphosis at a smaller mass seems to conflict with the absence of UV effects on the larval growth rates.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar life-history effects of UV exposure have been reported for other aquatic taxa, including amphibians (e.g. Pahkala, Laurila & Meril€ a 2001;Pahkala et al 2003) and cladocerans (Huebner et al 2013). The delayed metamorphosis at a smaller mass seems to conflict with the absence of UV effects on the larval growth rates.…”
Section: Discussionsupporting
confidence: 69%
“…) and cladocerans (Huebner et al . ). The delayed metamorphosis at a smaller mass seems to conflict with the absence of UV effects on the larval growth rates.…”
Section: Discussionmentioning
confidence: 97%
“…Similar UV‐induced fitness costs have been previously documented in D. magna (e.g. Borgeraas & Hessen, ; Huebner et al ., ) and many other aquatic organisms (reviewed in Bancroft et al ., ; Rautio & Tartarotti, ). ROS‐induced oxidative damage to proteins, lipids and DNA can lead to apoptosis and thereby explain reductions in fertility and survival rates (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that UV radiation affects cladocerans in several ways, such as reducing the number of offspring [24, 67, 68], changing swimming behavior [32, 69, 70], and causing visceral [71] and DNA damage [68, 72]. Some metabolic and physiological effects of sub-lethal UV doses on cladoceran species have also been noted, such as decreased/increased respiration rates [73], reduced activities of digestive enzymes, and reduced residence time of algae in the gut [41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unlikely that increased UVB doses will affect zooplankton mortality rates dramatically in nature. Sub-lethal damages, on the other hand, are likely more important than lethal effects, and may affect zooplankton in more subtle ways reducing their fitness [24, 25, 41]. …”
Section: Introductionmentioning
confidence: 99%